"Göteborgskravallerna" 2001 och polisens machoattityd - Liliequist, Marianne (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2004)
The author has carried out interviews with activists who in June 2001 participated in the demonstrations connected to the EU-conference in Gothenburg. The main theme in the respondents' stories is the traumatic experience of the conduct of the Swedish police force. Their macho manners was seen in their choice of strategy where they preferred aggressive confrontation to dialogue. It was also apparent in their sexist and racist threatening of the activists, in their verbal abuse and otherwise.